1997
DOI: 10.1021/ie970104r
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Water Organic Pollutants. Kinetic Modeling and Energy Efficiency

Abstract: Photocatalytic conversion of a model pollutant (methylene blue) is studied in a novel Photo-CREC reactor unit. The experiments developed allow us to investigate the suitability of an heterogeneous reaction model which accounts for the concentrations of the model pollutant both in the bulk and on the mesh-TiO 2 . In addition, a photochemical-thermodynamic efficiency factor (PTEF) is further examined, with the help of the enthalpy of • OH formation from water and oxygen and based on the analysis in the light ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 14 publications
1
50
0
1
Order By: Relevance
“…Experiments were developed in two types of reactors: (a) the Photo-CREC-Water-I reactor, where the catalyst is attached to fiber glass mesh (Serrano and de Lasa, 1997), (b) the Photo-CREC-II reactor, where the catalyst is suspended as a slurry (Salaices et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were developed in two types of reactors: (a) the Photo-CREC-Water-I reactor, where the catalyst is attached to fiber glass mesh (Serrano and de Lasa, 1997), (b) the Photo-CREC-II reactor, where the catalyst is suspended as a slurry (Salaices et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments performed using MeB have intrinsic advantages as MeB blue's color disappears as photoconversion progresses and provides a quick assessment of the reactor performance. Additional details about various experimental and analytical techniques are reported in Serrano and de Lasa (1997), Serrano (1998) and Salaices et al (2001Salaices et al ( , 2002.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have identified the existence of mass transfer limitations in many immobilized systems, such as tubular reactors [7], [8], annular reactors [9]- [11], rotating disc reactors [9], [12], and packed-bed reactors [7], [13], among others [14]. A commonly used model equation derived from first principles is a Langmuir-type equation based on volumetric flowrate Q [15], [16]:…”
Section: Introductionmentioning
confidence: 99%
“…The quantum yield was further modified into photochemical thermodynamic efficiency factor [77], which is given as:…”
Section: Introductionmentioning
confidence: 99%